Risk Value Analysis of Gold Futures Trading Investment using Fundamental Analysis, Technical Analysis, and Value at Risk - Hardiyanti, Widya; Darnius, Open (Journal of Research in Mathematics Trends and Technology, 2021)
This study was conducted to analyze the value of risk in trading Gold Trading Futures using Fundamental Analysis, Technical Analysis and Value at Risk. Fundamental analysis that uses Wage Income data other than the Agriculture Sector (Non-Farm Payroll), the conditions of the United States economy, and demand for gold prices in the world. Technical Analysis uses Moving Average Convergence / Divergence, Relative Vigor Index, and Pivot Points. Value at Risk is based on normal errors and skewness / kurtosis. The results of the analysis shown are the MACD Indicator has a truth level of 146 out of 226 days of analysis or 64.602%, the RVI Indicator has a truth level of 220 days from 226 days of analysis or 97.345%, Fundamental Analysis has a truth level of 23 out of 23 Excited for a year or 100%. Based on the level of confidence = 95%, it can be concluded that the price of gold with the normal approach (Ψ_{normal}) = 1211.1984 and the price of gold with the skewness and kurtosis approach (Ψ_{SK}) = 1247.34072.